Дослідження у Києві по провулку Десятинному, 3А/Б, 5 Д - Козловський, А.О.; Ієвлев, М.М.; Крижановський, В.О. (Археологічні дослідження в Україні, 2009)
The paper presents the results of excavations at 3 А/Б, 5 Д Desyatynnyi Lane, an area of «the city of Volodymyr» where the Western Palace was situated. The data obtained shows that at the beginning of the 10 th c. the necropolis was situated here, then apparently at the end of the 10 th c. the palace was constructed, the time of destruction of which is debatable yet. Besides, several dwelling and husbandry structures of an Ancient Rus and of later periods were revealed here.